Chondrocutaneous helix rim advancement flap: two classical and two new modifications for very large defects of the ear. (22nd October 2014) - Valesky, E.M.; Kaufmann, R.; Meissner, M.
Abstract Background The plastic reconstruction of the ear after microscopically controlled tumor surgery is a particular challenge. The chondrocutaneous helix rim advancement flap (CHRAF) is perfectly suited for the repair of different defects of the helix and even defects beyond. Objective Here, we describe two known and two new modifications of the CHRAF that enlarge the scope of application in tumor surgery of the ear. Methods We demonstrate the different techniques and practical application of the repair and evaluate the benefits and limitations. Results The CHRAF and its modifications is an excellent method for repair of various defects of the helical region of the ear. Conclusion The CHRAF and its modifications proves to be an good alternative to other methods of closure by preserving the anatomical contour and mechanical and acoustic functions in a single‐staged procedure with excellent aesthetic results. The two new modifications we introduced here, enlarge the known armentarium for very large defects of the upper pole and the mid‐helix of the ear.